2018
DOI: 10.1002/asia.201801175
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Enhancement in Boron Uptake Within Glioblastoma Cells With Carboranyl–Indole Carboxamides

Abstract: Novelb oron-rich, carboranyl-indolec arboxamide ligands were prepared and found to effectively target the 18 kDa translocator protein (TSPO), an upregulated mitochondrial membrane-bound protein which has been observed in variety of tumor cell lines and its expression appears to be proportionalt ot he degree of tumorigenicity, emphasizing ak ey role in cancer cell proliferation.B oth boronated compounds displayed remarkably high affinities for the TSPO. In addition, the in vitro uptake of these compoundsi nto T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A follow-up study reported two carborane-containing indole carboxamide TSPO ligands with even better uptake and toxicity profiles; plans for in vivo studies are currently in the pipeline. [48] Over the years, we have also reported on the synthesis of TSPO ligands not based on the pyrazolopyrimidine scaffold. Taking inspiration from a 1996 study by Campiani and co-workers, [49] we synthesised a library of 10 pyrrolobenzoxazepines to better understand their binding and functional properties at TSPO through systematic in vitro investigations (structures of three of these compounds that are shown in Fig.…”
Section: Relationships Of Tspo Ligandsmentioning
confidence: 99%
“…A follow-up study reported two carborane-containing indole carboxamide TSPO ligands with even better uptake and toxicity profiles; plans for in vivo studies are currently in the pipeline. [48] Over the years, we have also reported on the synthesis of TSPO ligands not based on the pyrazolopyrimidine scaffold. Taking inspiration from a 1996 study by Campiani and co-workers, [49] we synthesised a library of 10 pyrrolobenzoxazepines to better understand their binding and functional properties at TSPO through systematic in vitro investigations (structures of three of these compounds that are shown in Fig.…”
Section: Relationships Of Tspo Ligandsmentioning
confidence: 99%
“…In BNCT, TSPO is a potential target for tumor targeting, and several carborane-containing TSPO ligands have been reported. , Carborane has been used as a boron source for BNCT, because of its high boron content and ease of organic moiety conjugation via c-c bonds using carbon atoms contained within the boron cluster structure. , However, carborane exhibits very high toxicity and very low water solubility, and carborane based compounds are not used in clinical studies.…”
mentioning
confidence: 99%